CLINICAL CASE OF DIFFERENTIAL DIAGNOSIS OF HYPOGLYCEMIA SYNDROME - Епифанова, Елизавета Эдуардовна; Еленская, Татьяна Сергеевна; Павленко, Владимир Вячеславович; Каменева, Евгения Александровна; Кокоулина, Юлия Андреевна (Medicine in Kuzbass, 2024)
The article presents a clinical case of insulinoma, which is the most common, hormone-producing tumor of the pancreas, manifested by hyperinsulinemic hypoglycemia. The prevalence of insulinoma in the general population is estimated to be about < 1 : 250000 cases. The manifestations of insulinoma often mimic diseases of the nervous system and the disease is mistaken for epilepsy, psychosis, or cerebrovascular disease, which leads to a delayed diagnosis. The most significant for diagnosis is the presence of the Whipple triad and the 72-hour fasting test. Here is a clinical case of differential diagnosis of hypoglycemia syndrome in a patient with insulinoma.